Co-liquefaction of Prosopis juliflora with polyolefin waste for production of high grade liquid hydrocarbons. (February 2019) - Arun, Jayaseelan; Gopinath, Kannappan Panchamoorthy; SundarRajan, PanneerSelvam; JoselynMonica, Marudai; Felix, Vargees
Highlights: Prosopis juliflora was liquefied with Polyolefin waste for bio-oil production. Hydrothermal liquefaction produced 61.23%wt of bio-oil. Bio-oil had 88.23% purity (petro-diesel) with 78% energy recovery efficiency. HTL wastewater had low weight acids, suggests effective reusability. Abstract: In this study, co-liquefaction (HTL) of Prosopis juliflora (PJ) biomass with polyolefin waste (PO) was performed to produce bio-oil. HTL on bio-oil yield was studied at varying PJ to PO ratios (0:1, 1:0, 1:1, 2:1, 3:1, 4:1 and 5:1) and temperatures from 340 to 440 °C. Bio-oil and HTL by-products were characterized by Mass Spectroscopy (GC–MS) and Fourier Transform Infrared Spectroscopy (FTIR) analysis. Bio-oil yield was around 61.23%wt at 420 °C for 3:1 blends with 3 wt% of HCl activated bentonite catalyst at 60 min holding time. HHV value was 46 MJ/Kg with 88.23% purity (petro-diesel). Additionally gas possessed 26.28% of Hydrogen gas, 45.59% of Carbon dioxide gas, 7.1% of Carbon monoxide gas, 8.12% of Methane gas and other elements. The energy recovery (78%) and carbon recovery (94%) was higher for 3:1 blends bio-oil than PO and PJ processed bio-oils. HTL wastewater possessed higher degree of reusability nature as HTL medium.